Note—Note on “Optimal Ordering Quantity to Realize a Pre-Determined Level of Profit” - Sankarasubramanian, E.; Kumaraswamy, S. (Management Science, 1983)
In this note we consider the one-period inventory model in which it is required to determine the order quantity which maximizes the probability of realizing a predetermined level of profit R. We give a condition for determining the optimal order quantity and provide explicit expressions for the optimal order quantity in three special cases.